NIKAH MUTAH: KONTEKSTUALISASI NARASI DAN NALAR NIKAH MUTAH - Ali Akhbar Abaib Mas Rabbani Lubis (Universitas Islam Negeri Mataram, 2020)
Researchers try to glance mutah marriage struggle, without having to justify in accordance with certain interests. Because we need to realize that up to date marriage has always been excellent in the struggle for Islamic law. This study entered into a qualitative cluster using literature study, using the ma’na-qum-maghza approach and analyzing framing models, using define problems, diagnose causes, make moral judgment, and suggest remedies. The results of the conclusion that the factors of mutah marriage, are: conditions of war, certain conditions far from domicile, avoid adultery. That also applies if urgent and emergency problems, such as: far from domicile because of work and study assignments, so forced to be far from the connection. For this reason, teenage free sex solutions have become commonplace, especially between men and women who share an interest in sexuality issues because of falling in love, mutah marriages are better used as alternatives (to make love) to avoid adultery. On the other hand, it is imperative that the practice of ultimate marriage can also open the way for men and women to practice in the name of religion.